1997
DOI: 10.1007/bf02765589
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of body mass index to intra-abdominal pressure as measured by multichannel cystometry

Abstract: The aim of the study was to identify the possible relationship between body mass index and intra-abdominal pressure as measured by multichannel cystometry. A retrospective chart review of patients presenting for urodynamic evaluation between January 1995 and March 1996 was carried out. Variables identified included weight, height, intra-abdominal pressure and intravesical pressure as recorded on multi-channel cystometrogram at first sensation in the absence of detrusor activity. Body mass index was defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
163
2
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(185 citation statements)
references
References 14 publications
10
163
2
10
Order By: Relevance
“…Across adult life, high BMI may lead to mechanical stress on the urogenital tissues. Noblett et al 36 has found strong correlations between BMI and intra-abdominal pressure and intravesical pressure that suggested obesity may cause a chronic state of increased pressure that stresses the pelvic floor. This supports the theory that BMI acts as an aggravating condition rather than a true risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Across adult life, high BMI may lead to mechanical stress on the urogenital tissues. Noblett et al 36 has found strong correlations between BMI and intra-abdominal pressure and intravesical pressure that suggested obesity may cause a chronic state of increased pressure that stresses the pelvic floor. This supports the theory that BMI acts as an aggravating condition rather than a true risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although the precise mechanisms behind the association between body weight and stress incontinence remain undecided, abdominal adiposity gives rise to increased intraabdominal pressure 27 and subsequently urethral sphincter closing pressure may be compromised. The increased prevalence and bother of urgency in obese women is not so readily explained and may be associated with hormonal and metabolic factors, increased fluid intake or may be secondary to somatic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Higher intra-abdominal pressures have been observed in patients with greater BMI, and this may stress the pelvic floor secondary to a chronic state of increased pressure [3]. Increased intra-abdominal pressure elevates pressure at maximum cystometric capacity, and decreases cough pressure transmission from the bladder to the urethra, as well as decreasing VLPP, which may contribute to the development of SUI in obese patients [7].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is one of the important risk factors for the development of urinary incontinence with old age, in addition to vaginal delivery, history of gynecological surgery, body mass index, menopausal status, smoking, and coffee and alcohol consumption [1,2]. Some authors have described an increase of intra-ab-dominal pressure in obese patients [3], and this phenomenon may stress the pelvic floor, possibly causing nerve and muscular injury that might lead to a higher prevalence of SUI [4]. Also, increased body mass index (BMI) is known to be associated with urge and mixed urinary incontinence [5].…”
Section: Introductionmentioning
confidence: 99%